Aspects on the mental health of riverside farmers from the lower São Francisco in Alagoas/Aspectos sobre a saúde mental de agricultores ribeirinhos do baixo São Francisco em Alagoas - Veronica de Medeiros Alves; Leilane Camila Ferreira e Lima Francisco; Alice Correia Barros; Izabelly Carollynny Maciel Nunes; Themis de Jesus Silva; Emerson Carlos Soares; Elton Lima Santos (Universidade Estadual de Alagoas, 2020)
The aim of this research was to evaluate the common mentaldisorderspresenceofagricultural and fisheries workers from the lower São Franciscoriverregion, Alagoas, Brazil. The importance of this study is justified by the increase in cases of Common Mental Disorders (CMD) in various parts of the world and in Brazil. In addition, it is a complex issue involving family farm work and its relationship tothe degradation, silting and reduction of water flow from the São Francisco River, which directly impacts the production and income generation of these workers. This is a cross-sectional descriptive quantitative epidemiological study. The sample consistedof 43 family, ramdomized,living in Porto Real do Colégio, Igreja Nova, Penedo and Piacabuçu. To collect data related to mental health problems, the questionnaire with sociodemographic variables and the identification questionnaire of psychiatric disorders at the attention level were used. Primary Self Report Questionnaire (SRQ-20). The survey results were analyzed using the SPSS version 20 statistical package. Descriptive statistics with a significance level of 5% were used. The survey identified a frequency of 7 (16.3%) people with CMD. The instrument items with the highest positive statements were: Lack of appetite; feels nervous, tense or worried; get tired easily; frequent headache; is easily frightened, has unpleasant sensations in the stomach. Most were male (40-93%), married (28-65.1%), cultivated rice (13-30.2%) and worked with fishing (7-16.3%). This research identified a considerable number of people with CMD, where the items of the instrument used point to the need to promote care focused on the signs and symptoms of anxiety that may be present in this community. Thus, this study can provide subsidies for the adoption of public policies for health promotionand improvement of the quality of life of family farming workers